PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA PADA TEMA PAHLAWANKU KELAS IV SD NEGERI 108306 GARBUS - Eva Permata; Beta Rapita Silalahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was a research and development with reference to the 4D model which is an extension of Define, Design, Development and Dissemination. The instrument used to collect data was a questionnaire. The data analysis technique was descriptive qualitative. This research produced a product in the form of Snakes and Ladders media for My Hero material in grade IV. The snakes and ladders media was declared suitable for use in grade as a learning medium. This can be seen based on the validation results by material experts, media experts, and teacher responses. The results of the material validation show that the average overall assessment of material experts on the media obtained a percentage of 88%, including the valid (feasible) category. The results of the media validation show that the average overall assessment of media experts on the media obtained a percentage of 80%, including the valid (feasible) category. The results of the teacher response validation show that the average overall assessment obtained a percentage of 98%. This percentage is included in the very valid (very feasible) criteria. There was no revision to the student response to the snake and ladder media, and getting a percentage of 96% means that the media developed is “very valid” and can be applied as a medium for the teaching and learning process in schools.